Performance of a Big Scale Green House Type Dryer for Coffee Drying Process - Sukrisno Widyotomo (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2014)
Dying is one of important steps in coffee processing to produce good quality. Greenhouse is one of artificial drying alternatives that potential for coffee drying method cause of cleans environmental friendly, renewable energy sources and chippers. Indonesian Coffee and Cocoa Research Institute has developed and testing a big scale greenhouse type dryer for fresh coffee cherries and wet parchment coffee drying process. Greenhouse has 24 m length, 18 m width, also 3 m high of the front side and 2 m high of the rear side. The maximum capacity of greenhouse is 40 tons fresh coffee cherries. Fiber Reinforced Plastic (FRP) used as greenhouse roof that combined with I and C profile of steel. Fresh coffee cherries and wet parchment coffee from Robusta variety use as main materials in this research. The treatment of this research was 30 kg/m2, 60 kg/m2 and 90 kg/m2 for coffee density. String process has done by manual, two times a day in the morning and in the afternoon. As control, fresh coffee cherries and wet parchment coffee has dried by fully sun drying method. The result showed that a big scale greenhouse has heat drying efficiency between 29.9-58.2% depend on type and density of coffee treatments. On the full sunny day, greenhouse has produced maximum drying air temperature up to 52oC. In radiation cumulative level 4-5 kW-jam/m2 per day, 12.9-38.8 tons fresh coffee cherries or wet parchment coffee with 58-64% moisture content can be dried to 12% moisture content for 6 up to 14 days drying process. Slowly drying mechanism can be avoided negative effect to degradation of quality precursor compound. Capacity of the dryer can be raise and fungi can be reduce with application of controllable mechanical stirring in the greenhouse. Keywords: greenhouse, coffee, drying, quality